Inhalation during fire experiments: an approach derived through ECG - Sebastião, Raquel
During forest fire fights, firefighters are exposed to several pollutants at different concentrations, which can induce critical health problems. This study main goal is to estimate firefighters' pollutants inhalation when in operational scenarios by combining environmental and physiological information. Both exposures to CO (carbon monoxide) and physiological data, such as ECG (electrocardiogram), HR (Heart Rate) and body temperature, were monitored during firefighters' activities in experimental forest fire. From the QRS complex of ECG the ECG-derived respiration (EDR) was estimated and convoluted with pollutants concentration to estimate individual smoke inhalation. The analysis of smoke inhalations allowed to detect extensive exposures and to identify critical situations namely risk of faint due to smoke intoxication. Our results support the usefulness of continuous monitoring of both physiological and environmental information to prevent and detect hazardous situations while firefighters are in operational scenario like forest fires. The results encourage the development of a decision support system to be applied in real-time during firefighting scenarios.